Synopsis, Childhood shocks, safety nets and cognitive skills: Panel data evidence from rural Ethiopia - Berhane, Guush; Abay, Mehari Hiluf; Woldehanna, Tassew (International Food Policy Research Institute, 2016)
Using child-level panel data from rural areas of Ethiopia, we analyze effects of both economic and non-economic shocks on child cognition skills measured after the early childhood age window. We identify that drought, in particular, reduces child cognitive skills markedly. Food price inflation during the study period and divorce also have significant adverse effects on cognition. Promisingly, we find that the safety net program established by the Ethiopian government in 2005 to protect households from the economic effects of such shocks mitigated the reduction in cognitive skills associated with these shocks